Gender on the Run: Wanted Latinas in a Southern California Barrio. (July 2017) - Flores, Jerry; Camacho, Ariana Ochoa; Santos, Xuan
Recent research on systems of social control has demonstrated how African American men who live in segregated neighborhoods are disproportionately affected by their legal standing, especially in their attempts to avoid imprisonment when "on the run." However, missing from this analysis is the inclusion of how the intersection of race, class, gender, and other identities shape our understanding of being "on the run." Building on work in this area, we focus on the unique and understudied experiences that young Latinas face while attempting to avoid rearrests and recidivism within a working-class Latina/o barrio.